Vitamin D Supplementation Does Not Impact Resting Metabolic Rate, Body Composition and Strength in Vitamin D Sufficient Physically Active Adults - Romeu Montenegro, Karina; Cruzat, Vinicius; Melder, Hilton; Jacques, Angela; Newsholme, Philip; Ducker, Kagan (MDPI AG, 2020)
Supplementation with the most efficient form of Vitamin D (VitD3) results in improvements in energy metabolism, muscle mass and strength in VitD deficient individuals. Whether similar outcomes occur in VitD sufficient individuals’ remains to be elucidated. The aim of this study is to determine the effect of VitD3 supplementation on resting metabolic rate (RMR), body composition and strength in VitD sufficient physically active young adults. Participants completed pre-supplementation testing before being matched for sunlight exposure and randomly allocated in a counterbalanced manner to the VitD3 or placebo group. Following 12 weeks of 50 IU/kg body-mass VitD3 supplementation, participants repeated the pre-supplementation testing. Thirty-one adults completed the study (19 females and 12 males; mean ± standard deviation (SD); age = 26.6 ± 4.9 years; BMI = 24.2 ± 4.1 kg·m2). The VitD group increased serum total 25(OH)D by 30 nmol/L while the placebo group decreased total serum concentration by 21 nmol/L, reaching 123 (51) and 53 (42.2) nmol/L, respectively. There were no significant changes in muscle strength or power, resting metabolic rate and body composition over the 12-week period. Physically active young adults that are VitD sufficient have demonstrated that no additional physiological effects of achieving supraphysiological serum total 25(OH)D concentrations after VitD3 supplementation.